A descriptive study of the relationship between listening to music and exercise for South African individuals - Brown, Emma Luisa (The IIE, 2020)
Contemporary literature around the relationship between listening to music and exercise is quantitative and focused on the physiological effects of using music during exercise. There is a lack of literature around the psychological effects and motivation of music-listening in the context of exercise. The purpose of this research study was to gain a qualitative understanding of and expand on the knowledge about the psychological relationship between listening to music and exercise regarding the conditions of intrinsic motivation according to self-determination theory. This study made use of semi-structured interviews as a means of in-depth data collection about the subjective experiences of participants. The sample consisted of one female and two male South African individuals who listen to music when exercising, engage in regular exercise, speak English, and live in Kwa-Zulu Natal. Data was analysed thematically. Significant findings of this study were the perceived psychological effects of listening to music being improved endurance, energy, exercise ability, motivation, mood and mental state, focus, adrenaline, control, confidence, and enjoyability. Moreover, these effects, as well as the perceived ability to endure exercise, distraction effects of music, and the intrinsic motivation provided by music, were found as the psychological benefits of music-listening during exercise.
Keywords: Music; Exercise; South Africans